Glycoengineering in CHO Cells: Advances in Systems Biology. Issue 3 (12th February 2018) - Tejwani, Vijay; Andersen, Mikael R.; Nam, Jong Hyun; Sharfstein, Susan T.
Abstract : For several decades, glycoprotein biologics have been successfully produced from Chinese hamster ovary (CHO) cells. The therapeutic efficacy and potency of glycoprotein biologics are often dictated by their post‐translational modifications, particularly glycosylation, which unlike protein synthesis, is a non‐templated process. Consequently, both native and recombinant glycoprotein production generate heterogeneous mixtures containing variable amounts of different glycoforms. Stability, potency, plasma half‐life, and immunogenicity of the glycoprotein biologic are directly influenced by the glycoforms. Recently, CHO cells have also been explored for production of therapeutic glycosaminoglycans (e.g., heparin), which presents similar challenges as producing glycoproteins biologics. Approaches to controlling heterogeneity in CHO cells and directing the biosynthetic process toward desired glycoforms are not well understood. A systems biology approach combining different technologies is needed for complete understanding of the molecular processes accounting for this variability and to open up new venues in cell line development. In this review, we describe several advances in genetic manipulation, modeling, and glycan and glycoprotein analysis that together will provide new strategies for glycoengineering of CHO cells with desired or enhanced glycosylation capabilities. Abstract : Complex glycoprotein biologics are commonly produced in Chinese hamster ovary cells. Glycosylation of these therapeutics controls many of their pharmacological properties. This review elaborates systems biology advances, including genetic manipulation, computational models and glycan/glycoprotein analysis, for manipulating protein glycosylation in CHO cells. Advances in metabolic engineering of CHO cells for production of therapeutic glycosaminoglycans such as heparin are also described.